Implementation of Renewable Energy Indicators to Manage Water Supply Resources - Husein, Ismail; Surendar, A.; Kadyrov, Marsel A.; Heidary, Alireza; Mortazavi, Mohsen; Elveny, M. (IOS Press BV, 2022)
Water management policies are considered critical issues in various industries to provide relevant demand for urban areas. In this study, renewable energy indicators are used to determine the efficiency of each indicator on water management issues. Therefore, it is evident that these indicators would enable policymakers to make proper decisions and propose novel methods to manage water resources in developed areas. The implementation of harnessing technologies would be the most influential index in developing indicators in the water management system. It is crucial to rebuild and innovate new technologies to eliminate the unnecessary expenses of water treatment virtually. © 2022 - IOS Press. All rights reserved.
Keywords: environmental aspects; Harnessing technologies; policy makers; sustainable indexes